Analisis Determinasi Kinerja Keuangan Bank Umum Syariah Di Indonesia (Periode Januari 2016 – November 2020) - Hapsari, Hening Pratika Nila (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
Islamic commercial Banks in Indonesia continue to experience improvement because of the better performance level of Islamic banking in Indonesia. The increase in the performance of Islamic commercial banks in Indonesia is also influenced by the role of the people who entrust them to use the banking services they choose, especially customers who invest in the hope of getting profit back. Bank Indonesia has determined that one way to measure bank profitability is the return on assets (ROA). This study uses a quantitative analysis using secondary data types in the form of monthly data for 4 years 11 months, namely Return On Assets (ROA) data which is influenced by BOPO, NPF, NOM, FDR that occurs in Indonesia using the ECM (Error Correction Model). The results in this study are BOPO has a negative and insignificant effect on ROA, NPF has a negative and significant effect on ROA, NOM has a positive and significant effect on ROA, and FDR has a negative and insignificant effect on ROA on Islamic Commercial Banks in Indonesia